Pengaruh Pergaulan Buruk Terhadap Remaja yang Melakukan Seks Pranikah Di Minahasa Utara - Kasenda, Rinna Yuanita; N.Mogigir, Elizabet; E. Y. Makaambahe, Deria; Y.P Tiwa, Marcellino (Peneliti.net, 2024)
This study discusses the influence of the adult environment on premarital sexual behavior of teenagers in North Minahasa. The research results show that a negative friendship environment can influence teenagers to engage in casual sexual behavior. In conclusion, the adult environment plays an important role in the formation of adolescents' sexual attitudes and behavior. This research is a type of field research with a qualitative approach, then the research is analyzed using descriptive analysis, in order to find out the influence of the scope of adult friendships that the subject has with their premarital sexual habits with the victim so that they fall into criminal acts. This research was conducted at LPAK II Tomohon, the subjects were selected based on the relevance of the case to the research This research is grateful to the subjects who were willing to become research material, as well as to all contributors. The bibliography includes various articles and research on premarital sexual behavior in adolescents and the factors that influence it